Women and Homelessness: Winning and Losing in the Welfare State - Hunter, Caroline (feminists@law, 2013)
It has long been argued that homelessness is a gendered experience. Thus responses to homelessness by the state will impact differently on men and women. Drawing on the literature that examines the meaning of homelessness and responses to it, this paper will examine the implications of a rights-based system in England which strongly differentiates between those with and without children and the implications of this for homeless women, both with and without children. It will contrast this rights-based system with the responses of other welfare systems and their outcomes for women.